2014
DOI: 10.1016/j.jenvman.2014.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Quality of trace element contaminated soils amended with compost under fast growing tree Paulownia fortunei plantation

Abstract: The use of fast growing trees could be an alternative in trace element contaminated soils to stabilize these elements and improve soil quality. In this study we investigate the effect of Paulownia fortunei growth on trace element contaminated soils amended with two organic composts under semi-field conditions for a period of 18 months. The experiment was carried out in containers filled with tree different soils, two contaminated soils (neutral AZ and acid V) and a non contaminated soil, NC. Three treatments p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
5
13
0
1
Order By: Relevance
“…2), illustrating the benefits of amendment application in this degraded soil by the enhancement of the processes of natural attenuation of metal toxicity. The amendment provoked a clear improvement in soil quality in the studied soils, as indicated by increases in available nutrients and in biochemical indexes of microbial activity (Madejón et al, 2014). Other authors have observed similar results in different experiments with amendment application (Park et al, 2011), pointing out the benefits of quality material addition for plant productivity.…”
Section: Biomass Productionsupporting
confidence: 69%
See 1 more Smart Citation
“…2), illustrating the benefits of amendment application in this degraded soil by the enhancement of the processes of natural attenuation of metal toxicity. The amendment provoked a clear improvement in soil quality in the studied soils, as indicated by increases in available nutrients and in biochemical indexes of microbial activity (Madejón et al, 2014). Other authors have observed similar results in different experiments with amendment application (Park et al, 2011), pointing out the benefits of quality material addition for plant productivity.…”
Section: Biomass Productionsupporting
confidence: 69%
“…Recent studies have shown that some Paulownia species show a relatively high tolerance to the presence of high concentrations of trace elements in the soil (Jiang et al, 2012;Madejón et al, 2014). Species in the Paulownia genus are highly adaptive to a wide range of climate and soil conditions (Yadav et al, 2013), and their use has been proposed for the afforestation of semi-arid areas, given their relatively good performance even under low water irrigation regimens (García-Morote et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…7), which are the soils with the highest levels of organic matter content. This is in agreement with other works with remediated soils that showed that the activity of these two enzymes is mainly determined by the availability of organic C substrates (Caravaca et al, 2003;Madejón et al, 2014). In general, there was a trend for higher enzyme activities in the rhizosphere of S. marianum than in C. cardunculus or D. viscosa rhizospheres (Fig.…”
Section: Soil Ph Organic Matter and Microbial Activity After Plant Esupporting
confidence: 92%
“…Among amendments, biochar, a carbonaceous product obtained from the pyrolysis of biomass under low oxygen conditions, was shown as a good soil conditioner to ameliorate soil fertility, thus to promote plant growth [4]. Additionally to biochar, compost also has been demonstrated to improve soil conditions; this product is formed through microbial degradation, it is rich in humic substances, microorganisms and inorganic components [5]. However, both biochar and compost showed efficient sorption capacities towards metal cations but not to metal anions [6].…”
Section: Extended Abstractmentioning
confidence: 99%